Sustainability and foreign workers in Bosnia and Herzegovina: Addressing labor shortages and concerns over UN 2030 Agenda - Hamza Preljević; Ena Kazić-Çakar; Mirza Ljubović; Hana Šarkinović-Köse; Harun Halilović; Kenan Ademovic (Heritage and Sustainable Development)
This article examines the integration challenges faced by foreign workers in Bosnia and Herzegovina, based on qualitative data from 16 workers across various professions. It addresses how these workers perceive integration policies and the legal, bureaucratic, social, and cultural barriers they encounter. With a significant outflow of skilled labor from Bosnia, foreign workers play a crucial role in filling the workforce gaps. The European Migration Network predicts a need for 45 million qualified workers in Western Europe, including Bosnia, by 2030, prompting a high emigration rate from the Western Balkans, which, in turn, will increase the demand for foreign labor. This will, in turn, make it more complex for BiH to fulfill its commitment to the Agenda 2030, as set forth by the United Nations in 2015, through the 17 Sustainable Development Goals (SDGs). A low birth rate contributes to the increasing need to increase the labor force, which may ultimately result in social engineering. Although the number of foreign workers in Bosnia has increased, they experience limited access to integration programs and face social isolation and administrative hurdles, which this article analyzes and aims to emphasize better integration policies. Future studies can explore the social acceptance of foreign workers by the locals in Bosnia.